Odpowiedzi

2009-11-20T22:54:44+01:00
A) x(x²-4x+3)=0

Δ=4
x₁=0
x₂=4
x=0 v x=4

b)
(2x⁴-5x³)-(2x²+10x)=4
x³(2x-5) - 2x(2x-5) = 4
(x³-2x)(2x-5)=4

ktos inny bedzie wiedzial jak dalej, ja ide spac ; D
1 1 1
Najlepsza Odpowiedź!
2009-11-20T23:16:55+01:00
A)
x³ - 4x² + 3x = 0
x³ - x² - 3x² + 3x = 0
x²(x-1) - 3x(x-1) = 0
(x² - 3x)(x-1) = 0
x(x-3)(x-1) = 0
x = 0 ∨ x-3 = 0 ∨ x-1 = 0

x = 0 ∨ x = 3 ∨ x = 1

Odp. x∈{0, 1, 3}

b)
2x⁴- 5x³ - 2x² + 10x - 4 = 0
2x₄- 4x² - x³ + 2x - 4x³ + 8x + 2x² - 4 = 0
2x²(x²-2) - x(x²-2) - 4x(x²-2) + 2(x²-2) = 0
(x²-2)(2x² - x - 4x + 2) = 0
(x²-2)(2x² - 4x - x + 2) = 0
(x²-2)(2x(x-2) - 1(x-2)) = 0
(x²-2)(2x-1)(x-2) = 0
(x+√2)(x-√2)(x-½)(x-2) = 0
x = -√2 ∨ x = √2 ∨ x = ½ ∨ x = 2

Odp. x∈{-√2, ½, √2, 2}
2009-11-20T23:23:34+01:00
A) x 3 - 16 x 2 + 3x=0
b) 2x 4 - 5x 3 - 2x 2+ 10x -4= 0
16x 4 - 125x 3- 4x 2+ 10x - 4 =0

1 1 1